Perceção do adolescente com paralisia cerebral acerca da qualidade da vinculação - Sousa, Maria do Carmo (2014)
Background: Cerebral palsy is a syndrome affecting the adolescent and the family, which can change relationship patterns and the perception of the attachment to parents and peers. Objectives: To identify the disability-related differences in the perception of adolescents with and without cerebral palsy of the quality of attachment to parents and peers. Methodology: Descriptive/correlational study, with a random sample composed of 66 adolescents from Northern Portugal (33 healthy adolescents studying at a public school and 33 adolescents with cerebral palsy attending a Centre for Cerebral Palsy), who were intellectually capable of understanding the data collection instruments. Data were collected using the Inventory of Parent and Peer Attachment. Results: No statistically significant differences were found between groups in the overall attachment. The only statistically significant difference was found in the alienation dimension, referring to peers. The scores obtained in the trust and communication dimensions were high, while those found in the alienation dimension were low, which allowed concluding that adolescents in both groups perceived their attachment as being of high security. Conclusion: These results may be relevant to plan nursing interventions among adolescents with cerebral palsy as they provide a better understanding of the characteristics of their psycho-affective development.